Pelatihan Batik Cap Hasil Karya Penyintas ODGJ di Desa Wonorejo dalam Program Projek Kepemimpinan Mahasiswa PPG Prajabatan Universitas Negeri Malang - M. Sifaul Masruri; Miftakhul Umi Nadziru; Septiani Aisyah Ayu Paramita; Sayu Darmayanti; Sheila Alfania; Titik Wijayanti; Rizqi Anggun Kharisma; Lintang Tawakal; Rizky Amalia; Robby Arief Hadirizky Perwira; Muhammad Ardiansyah; Muhammad Ilham H.; Bayu Kurniawan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Batik is an intangible cultural heritage of Indonesia that is full of philosophical and symbolic values, and has economic potential that can be utilized in community empowerment activities. Wonorejo Village, Singosari District, Malang Regency, is one of the areas that develops the batik tradition as part of social inclusion efforts for survivors of mental disorders (ODGJ). Through the Jiwa Gerdu Sawah Posyandu, a stamp and ciprat batik training program was held to improve the skills, economic independence, and social integration of ODGJ survivors. This activity was carried out in the form of community service by PPG Prajabatan students of Malang State University for one month, involving nine ODGJ survivors and five posyandu cadres. The implementation method includes three stages, namely preparation, training implementation, and follow-up. The results of the activity showed that ODGJ survivors experienced various challenges, such as social stigma, limited access to work, and lack of productive activities. Through batik training which was carried out in a participatory and adaptive manner, participants showed improvements in aspects of skills, self-confidence, and social interaction. This program not only provides economic value through the batik products produced, but also contributes to the formation of a more inclusive and supportive environment for the psychosocial recovery of ODGJ survivors. Thus, the art of batik can be a strategic medium in empowering vulnerable groups towards independence and sustainable social reintegration.